Selective processing of eating, weight and shape related words in patients with eating disorders and dieters. - Cooper, M; Fairburn, C (1992)
The Stroop colour-naming task was used to investigate selective processing of eating, weight and shape related words in two groups of dieters, patients with anorexia nervosa, patients with bulimia nervosa and a group of non-dieting controls. 'Normal dieters' were not different from the non-dieting controls. Dieters with a history of features of an eating disorder but no diagnosis and the patients with anorexia nervosa, like the patients with bulimia nervosa, showed selective processing of information related to eating, weight and shape.